Analysis of Student Receptions Against Sexual Violence Warta Ngapak Panturapost.com - Reza Abineri (Jurnal Ilmu Komunikasi Acta Diurna, 2022)
Online media such as Panturapost.com are able to change the concept of audiences in consuming news to online. The page with the highest number of readers is Warta Ngapak with the theme of sexual violence. That's why this study discusses the meaning of audiences/readers, especially news of sexual violence. This study uses qualitative research methods using Stuart Hall reception analysis to 14 santri community informants. They will read Warta Ngapak news about sexual violence. This reception analysis will focus on the meeting between the text and the reader where the reader is the producer of meaning. The purpose of this study was to examine the acceptance and meaning of adolescent students towards news texts. The process and technique of data collection used focus group discussions (FGD) and in-depth interviews with the pesantren community. The data analysis technique uses reception analysis with encoding-decoding of readers starting from interpretation, concretization, or critical of something that is read by the audience.